2014
DOI: 10.1371/journal.pone.0108941
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Transporter-2 (SGLT2; SLC5A2) Enhances Cellular Uptake of Aminoglycosides

Abstract: Aminoglycoside antibiotics, like gentamicin, continue to be clinically essential worldwide to treat life-threatening bacterial infections. Yet, the ototoxic and nephrotoxic side-effects of these drugs remain serious complications. A major site of gentamicin uptake and toxicity resides within kidney proximal tubules that also heavily express electrogenic sodium-glucose transporter-2 (SGLT2; SLC5A2) in vivo. We hypothesized that SGLT2 traffics gentamicin, and promotes cellular toxicity. We confirmed in vitro exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 74 publications
(116 reference statements)
1
43
0
Order By: Relevance
“…It has been suggested that AGs enter through other channels including transient receptor potential channels (75)(76)(77). The sodium glucose transporter SLC5A2 may also play a role in AG transport in the kidney (78). Whatever additional mechanisms of uptake are active, our data suggest that these mechanisms are universally under control of MET activity in hair cells.…”
Section: Discussionmentioning
confidence: 58%
“…It has been suggested that AGs enter through other channels including transient receptor potential channels (75)(76)(77). The sodium glucose transporter SLC5A2 may also play a role in AG transport in the kidney (78). Whatever additional mechanisms of uptake are active, our data suggest that these mechanisms are universally under control of MET activity in hair cells.…”
Section: Discussionmentioning
confidence: 58%
“…Aminoglycosides and GTTR can permeate through non-selective cation channels, including the MET channel expressed by hair cells (11, 12), and TRPV4 channels expressed by endothelial cells (70, 71). The sodium-glucose transporter-2 (SGLT2) traffics aminoglycosides into cells, and facilitates aminoglycoside-induced cytotoxicity (72). LPS treatment can upregulate endothelial cation channel expression (73).…”
Section: Discussionmentioning
confidence: 99%
“…ABRs to pure tones were used to ensure normal cochlear function prior to toxicity studies and determine threshold shifts following kanamycin treatment (20, 72). Briefly, needle electrodes were placed subcutaneously below the test ear, at the vertex, with a ground electrode near the paw.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, sodium-dependent glucose cotransporter 2 (SGLT2) was found to be specifically expressed in renal proximal tubules but weakly expressed in cochlear cells [80]. When SGLT2 expression in a murine kidney proximal tubule cell line was knocked down by siRNA, the cellular toxicity of aminoglycosides was reduced indicating an important role for SGLT2 in aminoglycoside tissue accumulation and nephorotoxicity [80]. Further investigation and understanding of aminoglycoside associated toxicity as well as chemical development of less toxic derivatives are required to alleviate the toxic effects and improve the antimicrobial benefits of aminoglycosides.…”
Section: Susceptibility To Aminoglycosidesmentioning
confidence: 97%
“…It has been reported that binding of amikacin to the endocytic receptor megalin and uptake of aminoglycosdies via the transient receptor potential vanilloid subtype 1 (TRPV1) channel and TRPV4 results in the accumulation of amikacin and other aminoglycosides in renal proximal tubules and hair cells leading to nephortoxocity and ototoxicity [78,79]. In another study, sodium-dependent glucose cotransporter 2 (SGLT2) was found to be specifically expressed in renal proximal tubules but weakly expressed in cochlear cells [80]. When SGLT2 expression in a murine kidney proximal tubule cell line was knocked down by siRNA, the cellular toxicity of aminoglycosides was reduced indicating an important role for SGLT2 in aminoglycoside tissue accumulation and nephorotoxicity [80].…”
Section: Susceptibility To Aminoglycosidesmentioning
confidence: 98%